Evolutionary diversification of defensins and cathelicidins in birds and primates. (May 2023) - van Dijk, Albert; Guabiraba, Rodrigo; Bailleul, Geoffrey; Schouler, Catherine; Haagsman, Henk P.; Lalmanach, Anne-Christine
Abstract: Divergent evolution for more than 310 million years has resulted in an avian immune system that is complex and more compact than that of primates, sharing much of its structure and functions. Not surprisingly, well conserved ancient host defense molecules, such as defensins and cathelicidins, have diversified over time. In this review, we describe how evolution influenced the host defense peptides repertoire, its distribution, and the relationship between structure and biological functions. Marked features of primate and avian HDPs are linked to species-specific characteristics, biological requirements, and environmental challenge. Highlights: Genome size restraints governed diversification of avian cathelicidin genes and fewer β-defensin genes. In contrast to primates, the cathelicidin repertoire is more diverse, but restricted in its distribution. The conservation of multiple avian cathelicidin genes among different clades infer adaptations to niche biological functions. β-sheet conservation in primate and avian β-defensins supports a convergent evolution towards receptor-mediated functions.